Pattern and Expression of Oral Mucosal Lesions in a Pediatric Population - Soni, Tamanna; Galhotra, Adaa; Panwar, Pooja; Bhagat, Ankur; Rava, Diganta; Gautam, Yogita (Journal of Neonatal Surgery, 2025)
Background: The study was conducted to assess the pattern and expression of oral mucosal lesions in a pediatric population. Material and methods: This study comprised of 100 subjects of less than 15 years of age who underwent oral clinical examination for oral lesions. The procedure of this study was explained to all the subjects and all the participants were asked to give consent. All the participants were included in the study. The subjects underwent oral clinical examination and the prevalence of oral lesions was assessed. The findings had been tabulated. Statistical analysis was performed using SPSS software. Results: In this study, the most common lesion was eruption cyst accounting for 29% cases. Other lesions were ulceration (23%), dentoalveolar abscess (21%), gingivitis (16%) and geographic tongue (11%). There were 49 males and 51 females. Conclusion: The results of this study conclude that the most common lesion was eruption cyst. Other common lesions were ulceration, dentoalveolar abscess, gingivitis and geographic tongue